Of her own design - Willis, Birdie (Mad Cave Studios, 2024)
"In the small town of Holden, sixteen-year-old Brie Page has been struggling with a tremendous bout of writer's block. And that's a problem. One of many she has, actually. Parents that constantly fight, her former best friend/current bully Viv Kinsley, and the gorgeous new girl Kay Ardiger are causing a bit of stress. Brie used to hide from it all in her own worlds and stories, but that seems so far away now. Until an unexpected encounter with a mischievous bookseller, Ambrose Chance, gives Brie the extraordinary ability to go beyond her problems in life and bury them deep into three new stories. Too bad the whole town of Holden had to get caught up in it too when her stories come to life. Now, when the most important people in her life are stuck in fantastical tales, Brie needs to save them by diving into her worlds and facing her worries head-on. Which would be fine...if only she was better at writing endings."--Amazon.